Anatomical Considerations of Intramedullary Humeral Nailing and Lengthening - Schwarz, Gilbert Manuel (J Clin Med, 2020)
Intramedullary lengthening, in cases of extensive humeral shortening, offers the advantages of preventing external-fixator-associated problems. The humeral cavity, as the main parameter in nailing, however, has been neglected in recent literature. It was hypothesized that available implants might be too large and therefore increase the risk of intraoperative fractures. The aim of this cross-sectional study was to describe the humeral canal and how it might affect the choice of implant and the surgical approach. Thirty humeri (15 female, 15 male) from clinical patients and anatomical specimens were studied. Specifically, the medullary cavity width (MCW), cortical thickness (CoT), and the course of the medullary canal were examined. The smallest MCW diameters were found at the distal third of the humeral shaft with mean diameters of 10.15 ± 1.96 mm. CoTs of female humeri were significantly smaller than those of male humeri (p < 0.001). The mean angles of the pro- and recurvatum were 4.01 ± 1.68° and 10.03 ± 2.25°, and the mean valgus bending was 3.37 ± 1.58°. Before implanting a straight lengthening nail into a doubly curved humerus, X-rays and, in selected cases, CT-scans should be performed. The unique size and course of the humeral canal favors an antegrade approach in cases of intramedullary lengthening.